Understanding the Role of the Gut Microbiome in Brain Development and Its Association With Neurodevelopmental Psychiatric Disorders - Dash, Somarani; Syed, Yasir Ahmed; Khan, Mojibur R. (Frontiers in Cell and Developmental Biology, 2022)
The gut microbiome has a tremendous influence on human physiology, including the nervous system. During fetal development, the initial colonization of the microbiome coincides with the development of the nervous system in a timely, coordinated manner. Emerging studies suggest an active involvement of the microbiome and its metabolic by-products in regulating early brain development. However, any disruption during this early developmental process can negatively impact brain functionality, leading to a range of neurodevelopment and neuropsychiatric disorders (NPD). In this review, we summarize recent evidence as to how the gut microbiome can influence the process of early human brain development and its association with major neurodevelopmental psychiatric disorders such as autism spectrum disorders, attention-deficit hyperactivity disorder, and schizophrenia. Further, we discuss how gut microbiome alterations can also play a role in inducing drug resistance in the affected individuals. We propose a model that establishes a direct link of microbiome dysbiosis with the exacerbated inflammatory state, leading to functional brain deficits associated with NPD. Based on the existing research, we discuss a framework whereby early diet intervention can boost mental wellness in the affected subjects and call for further research for a better understanding of mechanisms that govern the gut-brain axis may lead to novel approaches to the study of the pathophysiology and treatment of neuropsychiatric disorders.